Trait anxiety mediates between emotion dysregulation and core psychopathology in borderline personality disorder - E. Kot; P. Grzegorzewski; B. Kostecka; J. Radoszewska; K. Kucharska (European Psychiatry, 2022)
Introduction Findings from previous studies have implicated various forms of emotion dysregulation (EDys), including difficulties in emotion regulation, as important for the development and maintenance of borderline personality disorder (BPD). In addition, comorbid anxiety and depressive psychopathology has been found to contribute to the severity of BPD symptoms in this disorder.